The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s13524-015-0426-x
|View full text |Cite
|
Sign up to set email alerts
|

War and Marriage: Assortative Mating and the World War II GI Bill

Abstract: We exploit between-cohort variation in the probability of military service to investigate how World War II and the G.I. Bill altered the structure of marriage, and find that they had important spillover effects beyond their direct effect on men's educational attainment. Our analyses further motivate instruments to help identify the effect of men's education on spousal "quality." We find that the additional education received by returning veterans allowed them to "sort" into wives with comparably higher levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 55 publications
(42 reference statements)
2
23
0
Order By: Relevance
“…This is due to earlier eligibility for a retirement pension for the veteran (at age 60, compared to 65 for non-veterans) and for his wife (55 compared to 60), as well as disability compensation payments for many veterans. In any case, the results do not support the suggestion that WWII service led to family disruption and dissolution, at least later in life (Damousi (Larsen et al 2015) and Vietnam (Conley and Heerwig 2013).…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…This is due to earlier eligibility for a retirement pension for the veteran (at age 60, compared to 65 for non-veterans) and for his wife (55 compared to 60), as well as disability compensation payments for many veterans. In any case, the results do not support the suggestion that WWII service led to family disruption and dissolution, at least later in life (Damousi (Larsen et al 2015) and Vietnam (Conley and Heerwig 2013).…”
mentioning
confidence: 56%
“…1 Matthew Larsen et al (2015) found that this increased college participation also led veterans to marry more educated wives. They also found no effect on marital status at 1970.…”
mentioning
confidence: 99%
“…We might expect, given their relatively low income in the decades following the war, that draft-eligible fathers would match with lower-skilled mothers. Still, at least one paper has concluded that the additional education received by returning (WWII) veterans sorted men into higher-skilled wives (Larsen et al, 2015). military service, on average, would need to reduce annual earnings by an implausibly large amount, on the order of $100,000, which is close to 300% of the mean earnings of control sons.…”
Section: Discussion Of Mechanisms and Interpretationmentioning
confidence: 99%
“…Similarly, explanations that are based on effects of war service on the quality of children via a demographic channel -say, if there are effects of war service on matching in marriage markets (e.g. Larsen et al 2014) -must contend with the same issue that arises in the material incentives channel we have analyzed: in the data, it seems that a father's veteran status increased the quality of children when it comes to labor market opportunities. More generally, any demographic explanation would have to be consistent with the opposite effects we find for service during and outside of wartime.…”
Section: Demographymentioning
confidence: 96%